2018
DOI: 10.12968/bjon.2018.27.22.1321
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perspectives on opt-out consent for observational research: systematic review and focus group

Abstract: 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Although an opt-out method of contacting patients such as described in this research can be ethically controversial and limited by government regulations in some jurisdictions, the literature shows that most patients consider it an acceptable approach. 18,128 3.5. Sample size Our review of chronic pain studies found small sample sizes to be problematic.…”
Section: Cohort Identification and Characterizationmentioning
confidence: 99%
“…Although an opt-out method of contacting patients such as described in this research can be ethically controversial and limited by government regulations in some jurisdictions, the literature shows that most patients consider it an acceptable approach. 18,128 3.5. Sample size Our review of chronic pain studies found small sample sizes to be problematic.…”
Section: Cohort Identification and Characterizationmentioning
confidence: 99%
“…However, no patient to date has opted out. We have conducted qualitative research on patient preferences regarding opt out consent in our patient population [3], and hence we expect this number to remain extremely low.…”
Section: Construction and Contentmentioning
confidence: 99%
“…As described, methods for recruitment and retention are broadly categorized as active and passive methods, with active methods being preferable and having a lower participant burden. Using the example of sending introductory letters for the purpose of recruitment, active recruitment would entail the research team contacting potential participants after a predetermined number of days that would allow the patient to opt out of being approached ( 156 ). Passive recruitment would entail potential participants having to opt in and contact the research team directly to learn more, leaving the research team being unable to reach out otherwise.…”
Section: Toolkit: Suggested Enhancements For Research Protocol Implementationmentioning
confidence: 99%